Higher Education outcomes for Indigenous Australians : barriers and enablers to participation and completion. - Rigney, Lester-Irabinna; Neill, Bec (Australia. Office for Learning and Teaching, 2018)
This report presents the methods and findings from the second and third phases of the project for the fifth case study institution. The second phase of the project explored, through semi-structured interviews, the experiences of staff and students at the case-study university and identified enablers and barriers to higher education participation common to their experiences. The third phase of the project at the case study site used a site specific participatory action approach to explore existing best practice across the institution and co-construct an evidence-based best practice model for supporting and retaining Aboriginal students undertaking higher education. [Publisher summary, ed]